Top‐Down Electrochemical Synthesis of Nanoporous Metal Nanosheets from Nonlayered Alloy Precursors - Chatterjee, Swarnendu; Gawas, Ramchandra; Snyder, Joshua (Advanced engineering materials, 2024)
Two‐dimensional (2D) nanomaterials are an attractive class of multifunctional materials owing to their unique chemical, electronic, and structural properties. Bottom‐up formation of 2D nanomaterials (solution processing, atomic‐layer deposition, chemical vapor deposition, etc.) affords direct control of material morphology and chemistry, tailoring their exhibited physicochemical properties. These methodologies, however, have limited throughput. The reduced output and expense of these bottom‐up methodologies limit their economic viability for mass production of multifunctional 2D nanomaterials. Top‐down approaches, through either exfoliation/delamination of a layered material or initiated targeted removal of a sacrificial component, are much more amenable to high production rates. Herein a unique electrochemical dealloying protocol is presented and analyzed for the synthesis of nanoporous iridium nanosheets (npIrx‐NS) from nonlayered, homogeneous alloy precursors. Through observations of combinatory effects of dealloying electrolyte and precursor alloy compositions, insights into the mechanism of formation and evolution of nanoporosity in free‐standing 2D flakes are gained. Nanoporous nanosheets of iridium can be formed through a top‐down methodology involving simultaneous formation of nanoporosity through dealloying and exfoliation of nanoporous nanosheets from a parent alloy. Exfoliation of nanosheets occurs through a combination of fast dissolution of a sacrificial component, induced by high potentials and halide anions in the electrolyte, and evolving stress‐induced fracturing of the nanoporous morphology.